Do Diverted Kids Stay Out of Trouble?: A Longitudinal Analysis of Recidivism Outcomes in Diversion (Journal of Applied Juvenile Justice Services, 2019)
This study evaluates the effectiveness of a police diversion program between 2008 and 2016.Youth participating in the diversion program were compared to youth not participating in diversion on the probability of, and time to, second offense using unadjusted comparisons at 6, 12, 18, 24, and 36 months, unadjusted lifetable comparisons of time to second arrest, and Cox multivariate proportional hazards regression models. Diverted youth had significantly fewer second offenses. The rate of recidivism among diverted youth was lower than non-diversion youth at all time periods in unadjusted models, and statistically significant at 6 months, 12 months, and 18 months.